An Improvement in Congestion Control Using Multipath Routing in Manet (Global Journal of Computer Science and Technology, 2012)
The ad hoc connections, which opens many opportunities for MANET applications. In ad hoc network nodes are movable and there is no centralised management. Routing is an important factor in mobile ad hoc network which not only works well with a small network, but also it can also work well if network get expanded dynamically. Routing in Manets is a main factor considered among all the issues. Mobile nodes in Manet have limited transmission capacity, they intercommunicate by multi hop relay. Multi hop routing have many challenges such as limited wireless bandwidth, low device power, dynamically changing network topology, and high vulnerability to Failure. To answer those challenges, many routing algorithms in Manets were proposed. But one of the problems in routing algorithm is congestion which decreases the overall performance of the network so in this paper we are trying to identify the best routing algorithm which will improve the congestion control mechanism among all the Multipath routing protocols.
Keywords: disjoint multipath; multi hop; reliability; congestion control; optimization